2018
DOI: 10.1007/s10549-018-4857-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements and fatigue in patients with breast cancer: a systematic review

Abstract: Dietary supplements or diet patterns are seldom used to treat fatigue in patients with breast cancer. The results of this review showed that guarana extract and a diet rich in whole foods, omega-3 fatty acids, fruits, and vegetables could be used to treat CRF in patients with breast cancer. The studies had a low risk of bias with high-quality evidence on the efficacy of the interventions in treating fatigue in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Despite the large theoretical rationale from animal and in vitro models for therapeutic use of anti-inflammatory diets in fatigued patients, and also some interesting and promising results from human trials, the evidence in humans is rare. Most of all, systematic reviews, which investigated the effects of different nutritional interventions on idiopathic fatigue as well as disease-related fatigue, share this conclusion [41,53,85,94,110], with the exception of studies in patients with cancer [14,86] or SLE [63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the large theoretical rationale from animal and in vitro models for therapeutic use of anti-inflammatory diets in fatigued patients, and also some interesting and promising results from human trials, the evidence in humans is rare. Most of all, systematic reviews, which investigated the effects of different nutritional interventions on idiopathic fatigue as well as disease-related fatigue, share this conclusion [41,53,85,94,110], with the exception of studies in patients with cancer [14,86] or SLE [63].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, current investigations show that there are new techniques available (including nanoparticles) that make it possible to apply higher vitamin doses to treat fatigue without negatively affecting chemotherapy [144]. Nonetheless, adverse side effects are more often described in administration of high-dose single nutrients than in the context of a combined therapy or whole diet [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of maintaining a normal weight through a diet is a factor of good prognosis [35], whereas weight gain after the diagnosis of breast cancer is associated with a higher mortality rate, further increased in case of a weight gain of 10% or more [37]. If food supplements are debated in the literature [38], patients have a particular interest in them based on the frequency of citation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these PUFA is more varied. While Holmes et al [56] showed no relation between fish consumption and breast cancer, recent studies confirmed the positive impact of n-3 fat on not only inhibiting [67,68], but also reducing fatigue [69], in breast cancer patients. In contrast to the large number of studies that confirmed the positive effects of n-3 PUFA on these two major chronic diseases, other research findings reported neutral, inconclusive or even possible negative effects [62].…”
Section: Metabolic Pathways Human Health Benefits and Recommendedmentioning
confidence: 99%